2021
DOI: 10.1029/2020je006692
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Chemical Evolution of Small, Shallow Water Bodies in Europa's Ice Shell

Abstract: Europa's geologically young surface has been modified by a myriad of geologic processes over at least the last 100 Myr (Bierhaus et al., 2009). Of the many resulting geologic features, the youngest appear low albedo and reddish in color, likely due to hydrated salts (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
117
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(131 citation statements)
references
References 82 publications
13
117
1
Order By: Relevance
“…We have shown that there exists a distinct and quantifiable relationship between the thermochemical environment of the ice–ocean interface at the time of solidification and the properties of the ice that forms. With the likelihood of ongoing hydrological activity within Europa’s ice shell in the form of lenses (B. E. Schmidt et al., 2011; Spaun et al., 1998), sills (Chivers et al., 2020; Craft et al., 2016; Manga & Michaut, 2017; Michaut & Manga, 2014), dikes, fractures (Dombard et al., 2013; Rudolph & Manga, 2009; Walker et al., 2014), and plumes (Jia et al., 2018; Sparks et al., 2016), understanding the characteristics of ice formed in an array of thermal environments is imperative in constraining the mechanical, dielectric, and eutectic properties of refrozen features. The presence of salt alters the rheological properties of ice (Assur, 1958; Durham et al., 2005; McCarthy et al., 2011) and could facilitate the reactivation of fractures as well as the dynamics of solid‐state convection in the ductile portion of the ice shell (e.g., Buffo et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that there exists a distinct and quantifiable relationship between the thermochemical environment of the ice–ocean interface at the time of solidification and the properties of the ice that forms. With the likelihood of ongoing hydrological activity within Europa’s ice shell in the form of lenses (B. E. Schmidt et al., 2011; Spaun et al., 1998), sills (Chivers et al., 2020; Craft et al., 2016; Manga & Michaut, 2017; Michaut & Manga, 2014), dikes, fractures (Dombard et al., 2013; Rudolph & Manga, 2009; Walker et al., 2014), and plumes (Jia et al., 2018; Sparks et al., 2016), understanding the characteristics of ice formed in an array of thermal environments is imperative in constraining the mechanical, dielectric, and eutectic properties of refrozen features. The presence of salt alters the rheological properties of ice (Assur, 1958; Durham et al., 2005; McCarthy et al., 2011) and could facilitate the reactivation of fractures as well as the dynamics of solid‐state convection in the ductile portion of the ice shell (e.g., Buffo et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The icy satellites of the outer solar system are some of the most enigmatic and inspirational bodies in planetary science, in large part due to their astrobiological potential (Des Marais et al., 2008; Hendrix et al., 2019; B. E. Schmidt, 2020). Ongoing geological activity and geomorphological features indicative of persistent subsurface water reservoirs suggests that these ice‐ocean worlds may house aqueous environments suitable for the formation and evolution of life (Chivers et al., 2020; Hand et al., 2009; Marion et al., 2003; C. D. Parkinson et al., 2008; Porco et al., 2006; B. E. Schmidt, 2020; B. E. Schmidt et al., 2011). One of the most promising of these bodies is Europa (Hand et al., 2007, 2009; Marion et al., 2003; B. E. Schmidt, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…HCN's density relationship with water and ice suggests that as a melt pond freezes from all directions, the HCN dynamics will operate differently at the bottom and upper interfaces. A key feature of our impact melt system is that it is a closed finite body of water, similar to the proposed pockets of water thought to cause chaos terrain on Europa (Schmidt et al 2011;Buffo et al 2020;Chivers et al 2021). SF2 assumes the mushy layer is atop an infinite ocean and that the rejected impurities will never significantly affect the bulk concentration of the ocean; however, the bulk concentration of a melt pond will become progressively more concentrated as it freezes.…”
Section: Application To Titanmentioning
confidence: 96%
“…Unlike salt, HCN is less dense than water and ice (Table 2; Haynes 2011). This relationship will invert the system such that impurities are buoyantly removed at the base of the melt pond, while at the top, gravity will not drive the removal of impurities (Chivers et al 2021). Similar scenarios have been studied in terrestrial magma chambers, where low-density melt is concentrated in the porous roof magma-rock interface during solidification (Worster 1990).…”
Section: Application To Titanmentioning
confidence: 99%
See 1 more Smart Citation